Antibacterial Potentials of Human Urine at Acidic pH 5 - Mehveen Iqbal , Aqeel Ahmad, Ghulam Fatima , Ejaz Ahmed3 , Shakeel A. Khan , Saira Yahya, Mehveen Iqbal , Aqeel Ahmad, Ghulam Fatima , Ejaz Ahmed3 , Shakeel A. Khan , Saira Yahya (Journal of Rawalpindi Medical College, 2017)
To identify factors determining susceptibility of individuals to urinary tract infections (UTIs). Methods: In this descriptive study , 55 hospitalized patients’ urine samples were analyzed. Presence of red blood cells , pus cells, epithelial cells, casts and crystals were observed and counted under per high power field (HPF) by microscopy. While pH, specific gravity, protein, leukocytes, nitrites, glucose, ketones, urobilinogen, blood and bilirubin, were analyzed using dipstick method. All the samples were streaked on CLED agar for isolation of bacteria; and SDA for yeast. Results: Twenty urine samples were found culture positive, of which 15 were from females and 5 from males. Cultures were isolated and identified as E. coli (11), Enterococcus (4), Klebsiella (3), Pseudomonas (1) and yeast (1). Interestingly, organisms were mainly isolated from urine samples having pH >5.5. In all the culture positive samples, pus cells were >20-40 /HPF. No patient with culture negative had urine pH 6.5 or above in the present study. Conclusion: The probability of bacteriuria (UTI) and pyuria (increase pus cells in urine) increases with rise in urine pH. Persons with urine pH5 are generally protected from UTIs. Thus mechanism/s needs to be elucidated.